The Strategic Value of Price Communication - Kramer, Andreas (Archives of Business Research, 2020)
Price communication is increasingly relevant in practice but is not sufficiently appreciated in research. Changed framework conditions, e.g. due to new price models in the context of digitalization or changed consumer behaviour, mean on the one hand that price communication has become more complex and on the other hand that new challenges on price communication have arisen. Overall, price communication should not be viewed as an isolated but as a pivotal part of overall pricing strategy.